EVALUATION OF DEPREDATION ACTIVITIES OF RODENT PEST ON MAIZE CULTIVATED IN SASA-AJIBODE FARM, IBADAN, SOUTHWEST, NIGERIA - Badmus, Hafiz Ayinde; Olubode, Oluseun Sunday; Ojo, Sharon (FUDMA JOURNAL OF SCIENCES, 2024)
Maize is a staple crop that is cultivated across different agro-ecologies in Nigeria. Maize adaptability and high yield potential, as well as its utility as a food, feed, and forage crop, clearly shows its significance. However, pests like rodent species remain an age-long challenge to its production by causing economic losses and low income for farmers. The study was carried out in Sasa – Ajibode farm. Systematic method of sampling was employed to observe and gather data in the study site. Quantitative data were collected by counting the number of damaged vegetative parts of the maize plant while qualitative data were collected by scoring observable damage signs on the maize. The result of the study revealed no observable signs of damage during the pre-flowering and post-flowering stages of maize cultivation in the study site during the dry and wet season in 2021. However, depredation activities of Ground squirrel (Xerus erythropus) by seed removal were observed during the sowing stage in the wet season. It can be concluded that rodent pest infestation is not the main threat to maize cultivation in the study site. However, environmentally-safe rodent management strategies should be adopted in the study area.
Keywords: Depredation activities; Rodent species; Maize cultivation; Season; Rodent damage